Camuflagem ortodôntica com dispositivos de ancoragem temporários ou cirurgia ortognática: parâmetros para a decisão - Monini, André da Costa [UNESP]; Peixoto, Adriano Porto [UNESP]; Maia, Savana de Alencar [UNESP]; Gandini Júnior, Luiz Gonzaga; Gonçalves, João Roberto [UNESP] (My University, 2010)
The polemical discussion between orthodontic therapeutic and surgical approaches with relation to borderline cases receives a new impulse with the emergence of temporary anchorage devices. This branch of Orthodontics has brought new treatment perspectives, but it has still been applied empirically, while the various factors involved in determining and conducting the treatment planning are neglected. The objective of the present study is to identify the several factors to be considered in both forms of treatment in order to provide the orthodontist with information that may contribute for the correct decision.

A polêmica discussão entre a abordagem terapêutica ortodôntica e a abordagem cirúrgica nos casos limítrofes ganha novo impulso com o surgimento dos dispositivos de ancoragem temporários. Esta vertente da Ortodontia trouxe novas perspectivas de tratamento, mas ainda se aplica de forma empírica e negligenciam-se os vários fatores envolvidos na determinação e condução do plano de tratamento. O objetivo deste trabalho é identificar os diversos fatores a serem considerados nas duas formas de tratamento para subsidiar o ortodontista de informações que possam contribuir para a correta decisão.
Orthodontic camouflage with temporary anchorage devices or orthognathic surgery: parameters for the decision
Keywords: Orthodontics corrective; Orthodontic anchorage procedures; Oral surgery; Ortodontia corretiva; Procedimentos de ancoragem ortodôntica; Cirurgia maxilofacial